Dielectric relaxation and conduction in the system Ba1-xLaxSn1-xCrxO3 - Upadhyay S.; Parkash O.; Kumar D. (My University, 2025)
Attempts have been made to synthesize the solid solution, Ba1-xLaxSn1-xCrxO3 for x ≤ 0.20 and study its electrical behavior. It has been found that a single phase solid solution forms for compositions up to x ≤ 0.10. The structure remains cubic. Grain size of the samples decreases with increasing x. Dielectric relaxation in these materials is attributed to reorientation of dipoles due to hopping of electrons among various oxidation states of Sn ions around oxygen vacancies. Using complex plane impedance analysis, it has been confirmed that dielectric relaxation and conduction occur by the same process.